Leadership Journey, Anti “Planga-Plongo” Character Education - Wakhudin Wakhudin; Eko Haryanto (UM Purwokerto Press, 2023)
The planga-plongo leader is a leader who does not know how to solve problems. The reason is that he did not get enough experience in various levels of leadership. This article aims to describe the leadership journey program that is expected to be able to overcome the planga-plongo attitude. The research using a qualitative approach with ethnographic methods was carried out by students of VI Class Madrasah Ibtida'iyah Muhammadiyah Patikraja, Banyumas, Central Java. The school permitted final grade students out of town on the eve of school graduation. They have the freedom to determine the city to which they were going. The results showed that, using information technology, they made preparations independently, including choosing the mode of transportation, booking tickets, determining local transportation, and various accommodations to be used. This leadership training provides a stimulus for children to be brave, honest, polite, fast and precise in making decisions. Various experiences of making decisions like this cause children to be unflinching when making decisions. It is recommended that building an anti-planga-plongo character is not only carried out during the implementation of the leadership journey, but also previous training with relevant activities.